1997
DOI: 10.1101/gad.11.17.2239
|View full text |Cite
|
Sign up to set email alerts
|

Binding specificity and in vivo targets of the EH domain, a novel protein–protein interaction module

Abstract: EH is a recently identified protein-protein interaction domain found in the signal transducers Eps15 and Eps15R and several other proteins of yeast nematode. We show that EH domains from Eps15 and Eps15R bind in vitro to peptides containing an asparagine-proline-phenylalanine (NPF) motif. Direct screening of expression libraries with EH domains yielded a number of putative EH interactors, all of which possessed NPF motifs that were shown to be responsible for the interaction. Among these interactors were the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
320
1
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(335 citation statements)
references
References 46 publications
11
320
1
1
Order By: Relevance
“…Although in all these contexts Numb functions as an endocytic adaptor protein, the exact role of Numb in endocytic trafficking remains an open question. Several studies have demonstrated that Numb interacts with two endocytic partners, α-adaptin and Eps15 [26,27], and is thereby involved in the regulation of clathrin-dependent endocytosis; but whether and how Numb regulates signal molecule degradation and intracellular trafficking through sorting endosomes are not clear. In this study, we unexpectedly identified cytosolic Numb as a novel regulator of EE homotypic fusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although in all these contexts Numb functions as an endocytic adaptor protein, the exact role of Numb in endocytic trafficking remains an open question. Several studies have demonstrated that Numb interacts with two endocytic partners, α-adaptin and Eps15 [26,27], and is thereby involved in the regulation of clathrin-dependent endocytosis; but whether and how Numb regulates signal molecule degradation and intracellular trafficking through sorting endosomes are not clear. In this study, we unexpectedly identified cytosolic Numb as a novel regulator of EE homotypic fusion.…”
Section: Discussionmentioning
confidence: 99%
“…In line with these discoveries, Numb was identified as an endocytic matrix protein [25] and is speculated to function as a homeostatic sensor, which regulates signaling attenuation, termination and maintenance in response to different cellular signals. Although all Numb isoforms bind the clathrin adaptor α-adaptin and other Eps 15-homology domain (EHD)-containing proteins involved in clathrin-dependent and clathrin-independent endocytosis [26][27][28][29], the detailed mechanisms by which Numb regulates endocytic trafficking remain to be characterized.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that monoubiquitylation of the receptor on multiple lysine residues robustly generates docking sites for endocytotic adaptor proteins possessing ubiquitin-binding domains. Adaptors, such as Eps15, may recruit receptors to clathrin-coated pits as they comprise both ubiquitin interacting motifs (UIMs) [20] and DPF motifs that couple to clathrin adaptors [AP2; [21]]. Recruited receptors are thus linked to AP2 complexes that drive the assembly of clathrin-coated vesicles (CCVs).…”
Section: Regulation Of Receptor Endocytosismentioning
confidence: 99%
“…The ligands to EH domains contain NPF cores, and the EH domain-ligand complexes seem to be involved in the regulation of molecular events underlying endocytosis (Salcini et al, 1997). It is curious that the NP6Y sequence is a general internalization signal for proteins (Bansal and Glerasch, 1991), and its similarity with the conserved cores of PTB, EH and WW ligands may not be coincidental.…”
Section: Ptb Rulesmentioning
confidence: 99%